Haloalkyne Chemistry - Jiang, Huanfeng; Zhu, Chuanle; Wu, Wanqing; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book presents efficient and practical methods for the synthesis of various functionalized organic molecules from haloalkynes through different reaction processes such as cross-coupling reactions, nucleophilic additions and cycloadditions. It consists of four chapters demonstrating interesting examples of these transformations, and showcasing the synthetic power of haloalkynes for rapid assembly of complex molecular structures. Most of the protocols allow multiple bond-forming events to occur in a single operation, offering opportunities to advance chemical synthesis and address the increasing demands for green and sustainable chemistry. It also presents a wide range of functionalized products, including many synthetically useful conjugated cyclic and acyclic structures that have potential applications in materials science, chemical biology and natural product synthesis. This book is a valuable reference not only for organic chemists, but also for biologists and materials scientists involved in the modern synthesis of organic compounds and materials. Huanfeng Jiang and Wanqing Wu are both Professors at the School of Chemistry and Chemical Engineering, South China University of Technology, China. Chuanle Zhu is a Postdoctoral Fellow at the School of Chemistry and Chemical Engineering, South China University of Technology, China.
Keywords: Chemistry, Organic; Optical materials; Medicinal chemistry; Organic Chemistry; Optical Materials; Medicinal Chemistry